Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1037/a0024364
|View full text |Cite
|
Sign up to set email alerts
|

Systemic mifepristone blocks reconsolidation of cue-conditioned fear; Propranolol prevents this effect.

Abstract: Reducing reconsolidation of reactivated traumatic memories may offer a novel pharmacological treatment for posttraumatic stress disorder (PTSD). Preclinical research is needed to identify candidate drugs. We evaluated the ability of postreactivation mifepristone (RU38486, a glucocorticoid antagonist), alone and in combination with propranolol (a beta-adrenergic blocker), both given systemically, to reduce cue-conditioned fear in rats. On Day 1, a 30-s tone conditioned stimulus (CS) was paired with an electric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 25 publications
3
60
1
Order By: Relevance
“…Our results are consistent with several studies investigating reconsolidation blockers either systemically (Debiec and Ledoux, 2004;Blundell et al, 2008;Taubenfeld et al, 2009;Pitman et al, 2011) or intracranially (Nader et al, 2000;Debiec and Ledoux, 2004;Ben Mamou et al, 2006;Jin et al, 2007). Indeed, it is accepted in the literature that the lack of spontaneous recovery, the selectivity to reactivated memories, and the presence of intact short-term memory are criteria that define the reconsolidation process.…”
Section: Reconsolidation Specificitysupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are consistent with several studies investigating reconsolidation blockers either systemically (Debiec and Ledoux, 2004;Blundell et al, 2008;Taubenfeld et al, 2009;Pitman et al, 2011) or intracranially (Nader et al, 2000;Debiec and Ledoux, 2004;Ben Mamou et al, 2006;Jin et al, 2007). Indeed, it is accepted in the literature that the lack of spontaneous recovery, the selectivity to reactivated memories, and the presence of intact short-term memory are criteria that define the reconsolidation process.…”
Section: Reconsolidation Specificitysupporting
confidence: 92%
“…Human work 2.4.1 MGH. On the basis of the animal results reported in previous annual reports and published in Pitman et al (2011), we decided to perform a double-blind, placebo-controlled study of prereactivation mifepristone's ability to reduce psychophysiologic responding during traumatic mental imagery in trauma-exposed human subjects. We analyzed data from 34 completed subjects who received PR mifepristone (n=14), NR mifepristone (n=10), or placebo (n=10), randomized and double-blind.…”
Section: ) (D)mentioning
confidence: 99%
“…Reactivation of a trauma memory and subsequent interference with its reconsolidation may offer a feasible and effective treatment strategy. Reconsolidation is governed by neurobiological processes similar to those of consolidation (Lee, Everitt, & Thomas, 2004), and is susceptible to pharmacological blockade (Debiec & Ledoux, 2004;Jin, Lu, Yang, Ma, & Li, 2007;Pitman et al, 2011;Przybyslawski, Roullet, & Sara, 1999;Kindt, Soeter & Vervliet, 2009). Studies exploring the efficacy of behavioral intervention, such as modifications to extinction learning within the reconsolidation window, have produced mixed results regarding interference with fear memory reconsolidation.…”
Section: Discussionmentioning
confidence: 99%
“…Pitman et al (2011) argue that when a memory is extinguished, it may be recovered through a reexposure to the unconditioned stimulus alone, or with the passage of time. On the other hand, it has been suggested that a memory that has undergone reconsolidation blockage is not recoverable, because the memory is thought to be erased, not extinguished.…”
mentioning
confidence: 99%
“…However, it impaired post-retrieval in long-term memory and the amnesia did not display any spontaneous recovery six days after retrieval. Pitman et al (2011) described how administration of certain reconsolidation-blocking drugs shortly after memory reactivation produced memory deficits in subsequent testing.…”
mentioning
confidence: 99%